African, Muslim refugee student teachers' perceptions of care practices in infant and toddler field placements. Issue 2 (3rd April 2018) - Massing, Christine
ABSTRACT: Within the context of the education-care divide in the field, numerous studies have affirmed that preschool teachers feel unprofessional when they assume a caring role yet believe that love and care are central to their work. However, immigrant/refugee teachers may experience this tensionality more acutely since their own cultural beliefs and values about caring for young children are situated outside the authoritative discourse, underpinned by western theories and practices. Framed by sociocultural-historical theory and concepts such as communities of practice, the purpose of this one-year ethnographic study was to enquire into how immigrant/refugee women studying in a Canadian early childhood college programme navigated the interstices between these discourses. Qualitative data were collected through field notes, spatial mapping, interviews, focus groups, and artefacts/documents. This article focuses on disjuncture between the cultural and religious understandings of care that five African, Muslim refugee women brought to their field placements in infant/toddler classrooms and the authoritative professional expectations, as related to mealtime practices. The findings elucidated how they interpreted care not only as a means of ensuring children's health and well-being, but also as a means of teaching religious and cultural values.